The role of autophagy in modulation of neuroinflammation in microglia. (5th April 2016) - Su, P.; Zhang, J.; Wang, D.; Zhao, F.; Cao, Z.; Aschner, M.; Luo, W.
Highlights: Microglial autophagy can influence the inflammatory response and survival of microglia. Microglial autophagy may be pro-inflammatory or anti- inflammatory. Many mechanisms involved in mediating the process of microglial autophagy. Abstract: Microglia have multiple functions in regulating homeostasis in the central nervous system (CNS), and microglial inflammation is thought to play a role in the etiology of the neurodegenerative diseases. When endogenous or exogenous stimuli trigger disorders in microenvironmental homeostasis in CNS, microglia critically determine the fate of other neural cells. Recently, it was reported that autophagy might influence inflammation and activation of microglia. Though the interaction between autophagy and macrophages has been reported and reviewed in length, the role of autophagy in microglia has yet to be reviewed. Herein, we will highlight recent advances on the emerging role of autophagy in microglia, focusing on the regulation of autophagy during microglial inflammation, and the possible mechanism involved.